Mechanisms of immune tolerance and liver disease - V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2009)
The aim of review. Antigen-specific T lymphocytes act as the main determinants of outcomes of acute and chronic liver diseases as, on one hand, they are involved in the early stage of disease in mechanisms of restriction of antigenic activity, on the other hand, these cells determine degree of immunopathologic responses. It is important to perceive clinical value of these immune mechanisms.Original positions. Antigen-presenting cell of the liver include dendritic cells, Kupffer’s cells, sinusoidal endothelial cells, stellate cells, epithelial cells (hepatocytes themselves). These antigen-presenting cells are capable to provide immune tolerance of the liver to infectious and non-infectious antigens by various mechanisms. CD8 + T-cells at persistent viral infections change their phenotype, preserving ability of control over a grade of viral load. Antibodies can activate CD8+ T- cells directly, without antigen-presenting cells that is accompanied by cytotoxic damage of the liver directly by CD8 + T- cells, or mediated by Kupffer’s cells activation. The platelet serotonin is involved in immunopathologic response, initiated by virus-induced CD8+ T-lymphocytes.Conclusion. In practice, at the patient’s bed, constant clinical-immunologic comparisons are essential for development of adequate treatment strategy to restrict the scale of immunopathological reactions. Sinusoids and microcirculation of liver act as springboard and target for immunopathological reactions.